2019
DOI: 10.1016/j.ajog.2018.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Gaining the patient perspective on pelvic floor disorders’ surgical adverse events

Abstract: BACKGROUND: The Institute for Healthcare Improvement defines an adverse event as an unintended physical injury resulting from or contributed to by medical care that requires additional monitoring, treatment, or hospitalization or that results in death. The majority of research has focused on adverse events from the provider's perspective. OBJECTIVE: The objective of this qualitative study was to describe patient perceptions on adverse events following surgery for pelvic floor disorders. STUDY DESIGN: Women rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…These symptoms have a wide-ranging impact on the quality of life of women, ranging from mild discomfort to paralysis and even severe functional impairment. [ 16 ] Pelvic floor ultrasound can perform imaging evaluation of female pelvic floor function to prevent and reduce the occurrence of early FPFD. At the same time, it can evaluate the pelvic floor rehabilitation effect, guide clinical early pelvic floor muscle training to improve the pelvic floor muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms have a wide-ranging impact on the quality of life of women, ranging from mild discomfort to paralysis and even severe functional impairment. [ 16 ] Pelvic floor ultrasound can perform imaging evaluation of female pelvic floor function to prevent and reduce the occurrence of early FPFD. At the same time, it can evaluate the pelvic floor rehabilitation effect, guide clinical early pelvic floor muscle training to improve the pelvic floor muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, if the planned surgery was not performed, even in the absence of complications, the women considered it as serious. In another qualitative study, women interviewed preoperatively expressed the need to "get back to normal" within the time period specified by their surgeon [13]; in the postoperative group, women categorized symptoms such as incontinence or constipation, or lack of improvement in sexual function as "very severe". As in our study, women ranked these functional disorders comparably to major surgical complications.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings may have been different if the women had been interviewed before their surgery. However, the study by Dunivan et al reported that women in the preoperative groups shared similar perspectives regarding surgical expectations [13]. The vignettes were presented in the same random order for all women, and several women commented that they became more and more alarmed as they completed the questionnaire and stopped before the end of the survey.…”
Section: Discussionmentioning
confidence: 99%
“…previously published conceptual framework for prolapse derived from patient focus groups. [7][8][9] An expert group consisting of 3 urogynecologists (VS, NS, MO) and one health measurement expert (KW) reviewed the initial set of 10 candidate domains derived from the previously published conceptual framework for prolapse (Fig. 2 and Fig.…”
Section: Augs Conference Report Nmentioning
confidence: 99%